Obstacle Avoidance System for Unmanned Underwater Vehicle using Fin System - Mohd Aras, Mohd Shahrieel; Md Basar, Mohd Farriz; Abd Azis, Fadilah; Ali, Fara Ashikin (2013)
An underwater glider is a type of an unmanned underwater vehicle (UUV). The movement of an underwater glider in the water is based on the buoyancy-propelled for float and fixed-winged for stabilizing the glider’s body. However, a fixed wing underwater glider has limitation to avoid hitting the obstacle in front of it. To overcome this problem, the application of fin system in underwater glider is needed. In this project, a methodology was introduced which is design a flexible fin system of an underwater glider for obstacle avoidance purpose. This project mainly focused on SolidWorks’s simulation and analysis of -30°, -45°, -60° for submerge and rise up at 30°, 45°, 60° to get the most suitable angle for the glider’s fin system to submerge and rise up. The UTeM underwater glider is modified from fixed to flexible wing. Hence, Peripheral Interface Controller (PIC) is used to program the movement of the glider’s wings for upward at 45°and downward at -45°in the water. Thus,a flexible fin system for obstacle avoidance is designed and applied in UTeM underwater glider.